2020
DOI: 10.3389/fmedt.2020.606079
|View full text |Cite
|
Sign up to set email alerts
|

Application of Biophysical Techniques to Investigate the Interaction of Antimicrobial Peptides With Bacterial Cells

Abstract: Gaining new understanding on the mechanism of action of antimicrobial peptides is the basis for the design of new and more efficient antibiotics. To this aim, it is important to detect modifications occurring to both the peptide and the bacterial cell upon interaction; this will help to understand the peptide structural requirement, if any, at the base of the interaction as well as the pathways triggered by peptides ending in cell death. A limited number of papers have described the interaction of peptides wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Physicochemical investigations on a number of AMPs and cell-penetrating peptides have demonstrated that, apart from charge and amphipathicity, their secondary structure and conformation play a crucial role in their ability to interact with cellular membranes ( 38 , 61 , 62 ). In particular, circular dichroism spectroscopy studies revealed a characteristic shift from a random, disordered secondary structure of TB_KKG6K in an aqueous environment to an α-helical conformation in the presence of sodium dodecyl sulfate, a fungal cell membrane surface mimetic ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Physicochemical investigations on a number of AMPs and cell-penetrating peptides have demonstrated that, apart from charge and amphipathicity, their secondary structure and conformation play a crucial role in their ability to interact with cellular membranes ( 38 , 61 , 62 ). In particular, circular dichroism spectroscopy studies revealed a characteristic shift from a random, disordered secondary structure of TB_KKG6K in an aqueous environment to an α-helical conformation in the presence of sodium dodecyl sulfate, a fungal cell membrane surface mimetic ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Physicochemical investigations on a number of AMPs and cell penetrating peptides have demonstrated that apart from charge and amphipathicity, their secondary structure and conformation play a crucial role in their ability to interact with cellular membranes (5759). In particular, circular dichroism spectroscopy studies revealed a characteristic shift from a random, disordered secondary structure of TB_KKG6K in an aqueous environment to an α-helical conformation in the presence of sodium dodecyl sulfate, a fungal cell membrane surface mimetic (7).…”
Section: Discussionmentioning
confidence: 99%